2000
DOI: 10.1046/j.1460-9592.2000.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic depression by halothane is age‐related in paediatric patients

Abstract: The hypothesis that young infants are more sensitive to the haemodynamic depressant effects of halothane compared with older children was tested. One hundred and sixty unpremedicated, ASA physical status I or II paediatric patients without cardiac or pulmonary disease were divided into five age groups: term neonates, 1-6 months, 6-24 months, 2-6 years and 6-12 years. Anaesthetic induction was achieved with halothane in oxygen and air via mask. Vecuronium 0.1 mg.kg-1 was administered intravenously. During normo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 33 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…SBP was recorded at baseline and at age‐appropriate 2 MAC halothane at a steady state after enough time to allow myocardial uptake of halothane. The results demonstrated that SBP decreased 30% in neonates and infants up to 6 months of age and 12%–15% in older children aged greater than 6 months to 12 years 11 . (Figure 4) Thus, these clinical studies demonstrated important hemodynamic depression by halothane in neonates and infants that significantly improved after 6 months of age, suggesting that functional myocardial maturation is attained by about 6 months.…”
Section: Clinical Studiesmentioning
confidence: 76%
“…SBP was recorded at baseline and at age‐appropriate 2 MAC halothane at a steady state after enough time to allow myocardial uptake of halothane. The results demonstrated that SBP decreased 30% in neonates and infants up to 6 months of age and 12%–15% in older children aged greater than 6 months to 12 years 11 . (Figure 4) Thus, these clinical studies demonstrated important hemodynamic depression by halothane in neonates and infants that significantly improved after 6 months of age, suggesting that functional myocardial maturation is attained by about 6 months.…”
Section: Clinical Studiesmentioning
confidence: 76%
“…15,16 Thus, at equipotent minimum alveolar concentrations of halothane or desflurane, the infant exhibits a greater decrease in MAP than does the older child. 17,18 The volatile anesthetics also cause a decrease of SVR that contributes to a decrease of MAP, with the effect of isoflurane being somewhat greater than that of sevoflurane or halothane in children with CHD and of desflurane in adults undergoing thoracotomy. 14,19 Evidence exists that volatile anesthetics also decrease PVR.…”
Section: Volatile Anestheticsmentioning
confidence: 99%
“…15,16 Thus, at equipotent minimum alveolar concentrations of halothane or desflurane, the infant exhibits a greater decrease in MAP than does the older child. 17,18…”
Section: Inhaled Anestheticsmentioning
confidence: 99%
“…Animal research at the time demonstrated that the cardiovascular depression associated with halothane was more severe in newborn animals than older ones, presumably because the immature myocardium was more sensitive to depression confirming the observation of an increased incidence of cardiac arrest in infants undergoing halothane general anesthesia . In a prospective study, Friesen demonstrated for the first time that at equipotent doses of halothane, blood pressure depression was greater in neonates and infants less than 6 months of age than in older children . Additional prospective studies of halothane induction of anesthesia in infants documented a mean decrease in blood pressure of 50% that could be attenuated by pretreatment with atropine to maintain heart rate .…”
Section: Introductionmentioning
confidence: 99%